Analysis of Iron and Polyphenols in Brown and Red Macroalgae from Antarctica - Yarlequé Chocas, Mirtha (2020)
Antarctica, the White Continent, is the refuge of typical species, where temperatures range from -85 to 2 oC, UV radiation can penetrate 30 m depth and salinity reaches 32-34%. Among these species, brown macroalgae (Pheophytas) and red macroalgae (Rhodophytas) are mainly evaluated as potential food and health resources for mankind. The macroalgae collected in February 2019 were taxonomically classified into 6 species: Desmarestia confervoides, (hacer la consulta con el autor/IMARPE) Desmarestia antarctica, Himantothallus grandifolius, Palmaria decipiens, Gigartina skottsbergii and Curdiea racovitzae. This research determined organic matter ranging from 12 to 20%, iron (atomic absorption), polyphenols and flavonoids (quantitative methods). The results revealed that the content of iron ranged from 6.72 to 154 mg%, polyphenols from 22.4 to 78.4 mg% and flavonoids from 10.09 to 21.31 mg%. We conclude that this research allowed us to know the iron and antioxidant characteristics of 6 most common Antarctic species.